The Untiring Eye: Automated Visual Inspection System for the Electronics Industry - Hendi Herlambang; Tri Ngudi Wiyatno; Zulfa Fitri Ikatrinasari; Uly Amrina; Kosasih Kosasih (Program Studi Teknik Industri S-1, Fakultas Teknik UPN Veteran Jakarta, 2025)
To address the escalating complexity of modern quality standards, this study introduces an automated vision inspection system for terminals in electronic components. The system employs a conveyor driven by a stepper motor, a photo-sensor for distance measurement, positioning guides, a vision sensor for quality detection, a cylinder for product ejection, and a PLC for control. Through computer logic, the system accurately differentiates between normal and defective products, segregating the latter into a reject box. Operating at a rate of 60 units per minute, the system demonstrated exceptional performance, achieving 100% accuracy in both vision inspection and cylinder ejection, and a 97.5% success rate in product positioning. The results of this study indicate the great potential of automated inspection systems in improving the efficiency and accuracy of electronic component production processes.